Convection-diffusion-reaction problems, SDFEM/SUPG and a priori meshes. (8th January 2008) - Stynes, Martin
First, a brief description of linear convection-diffusion-reaction problems is given. Then the Streamline Diffusion Finite Element Method (SDFEM, also known as SUPG) is introduced. Since its inception in 1979, this method has been the subject of a huge number of theoretical analyses and numerical investigations. The body of this survey paper is a comprehensive overview of what is known about the method where its strengths and weaknesses are discussed and recent theoretical results are included; in particular, Shishkin meshes are introduced and the behaviour of the SDFEM on these meshes is discussed.